The Effects of Leaderships Styles, Work-Life Balance, and Employee Engagement on Employee Performance - Putiri Bhuana Katili; W. Wibowo; Maruf Akbar (Quantitative Economics and Management Studies, 2021)
Employee Engagement is an important strategy on increasing company performance. The aims of this research is to elaborate influences of leadership styles and work- life balance to the employee engagement; also influence of employee engagement to the employee performance. To achieve this aim, the data was collected from 204 employees using questionnaire as instrument of research. The collected data was analyzed using SPSS and Structural Equation Modeling. This research conducted in steel industry. From this research can be concluded that work-life balance have most significant influence to employee engagement, and employee engagement have strong influence to the employee performance. By increasing leadership styles and work-life balance , the company could improve employee engagement. Therefore, the company management can utilize this research result for increasing employee performance and company competition.